Blood is thicker than baptismal water: A late medieval perinatal burial in a small household chest. (7th February 2021) - Cootes, Kevin; Thomas, Matthew; Jordan, David; Axworthy, Janet; Carlin, Rea
Abstract: The interment of stillborn infants in later medieval burial grounds stands at odds with Catholic Church Law, which forbade the inclusion of unbaptised children within consecrated ground. When perinatal remains occur within graveyards, their interpretation can be problematic. Did they live to be baptised, or do such examples represent clandestine burials? Historical documents indicate that some parents disobeyed the Church and secretly buried their offspring within consecrated ground. Proving such actions in the archaeological record, however, is another matter. This paper therefore investigates the discovery of a perinatal burial (Sk953) within a rural graveyard at Poulton in Cheshire, England, placed in a small household box. A multifaceted approach was used to interpret the varying strands of evidence. These comprised church law, the birth, container, orientation of the corpse, local topography, date of burial, and status of the graveyard when the infant was interred. The authors interpret the evidence as characteristic of a clandestine burial, and a rare expression of grief and love visible in the archaeological record.